Synthesis and Antibacterial Activity of Aminobenzylated Mannich Bases of Amides - Chaluvaraju, K.C.; Ishwarbhat, K. (Asian Journal of Chemistry, 2010)
In the present study some aminobenzylated mannich bases are reported and were obtained by reacting morpholine, benzaldehyde with various amides under mannich condition. The compounds were characterized and screeened for antibacterial activity.